Symmetry, Shared Labels and Movement in Syntax - Blümel, Andreas (Studia grammatica, 2017)
What is the trigger for displacement phenomena in natural language syntax? And how can constraints on syntactic movement be derived from interface conditions and so-called Third Factor principles? Within the Minimalist Program a standard answer to the first question is that it is driven by morphosyntactic features. This monograph challenges that view and suggests that the role of features in driving syntactic computation has been overestimated. Instead it proposes that "labeling"--The detection of a prominent element in sets formed by Merge -- plays a role in driving transformations, and labeling itself is understood to derive from an interplay of efficient computation and the need for a label at the Conceptual-Intentional systems. It explores this idea in four empirical domains: Long-distance dependencies, Criterial Freezing-phenomena, nested dependencies and ATB-movement. The languages considered include English, German and Hebrew.